Was the Missing 2013 WASDE Missed?. (9th November 2017) - Adjemian, Michael K; Johansson, Robert; McKenzie, Andrew; Thomsen, Michael; Stefanou, Spiro
Abstract: Government crop data have been shown to contribute to the efficient operation of agricultural commodity markets. In 2013, the USDA curtailed its crop report publication for the first time in decades due to an appropriations lapse, thereby offering the chance to study the impact on markets of missing government data. As expected, derivatives markets for corn and soybeans did not display characteristic short‐run patterns in terms of uncertainty resolution and price changes that are normally observed around scheduled USDA release times. We are unable to detect evidence of a prolonged period of heightened uncertainty, realized volatility around the missing report, or abnormal pricing errors in the absence of government data. However, an unsurprisingly large 2013 corn and soybean crop could confound that attempt.